Transfusão de sangue obtido de doadores anestesiados com cetamina e xilazina ou isoflurano em gatos hipovolêmicos - Cartana, Camila Basso (2010)
Blood transfusions are an important component of critical care. Obtaining blood for transfusion in cats is challenging due to its restless temperament, which makes unusual donors that do not require anesthesia during collection. Some anesthetic protocols have been recommended for cats donors. However, there are no studies about the possible consequences of the presence of anesthetics in blood transfused to hypovolemic recipients. The aims of this study are: to evaluate and compare the responses of hypovolemic cats to transfusion from blood donors anesthetized by isoflurane or combination of ketamine and xylazin; and evaluate a technique for monitoring arterial and venous blood pressures by dissecation and catheterization of carotid artery and jugular vein. We used 10 adult cats, mixed breed, weighing between 3 and 4.5kg. The animals integrated two groups: ISO (five donors and five recipients of blood collected under anesthesia by isoflurane) and CX (five donors and five recipients of blood collected under anesthesia by the combination of ketamine and xylazine). After anesthetic induction of the donor by one of the protocols, the blood was collected. The recipients were anesthetized with isoflurane and atracurium, and maintained on mechanical ventilation. The baseline data (t0) were measured by the following parameters: respiratory rate (RR), expired anesthetic concentration (ETIS), end-tidal carbon dioxide (ETCO2), central venous pressure (CVP), systolic, diastolic and mean blood pressure (SBP, DBP and MBP), heart rate (HR), arterial blood gas, blood count, glucose, urea and creatinine. The recipients had the hypovolemia induced by withdrawal of 20ml kg-1 of blood and then received blood from donors. The measurements were performed at baseline (t0), after hypovolemia (t1), immediately, 15, 30, 45 and 60 minutes after transfusion (t2, t3, t4, t5 and t6), and laboratory tests carried out only on t0, t1, t2 and t6. Data were subjected to analysis of one-way with multiple repetitions (ANOVA) followed by comparison by Tukey test to determine the statistical differences between means over the time in each group, as well as the means of each time between the groups. Differences were considered statistically significant when P ≤ 0.05. The group CX presented CVP significantly higher than the ISO group after transfusion and in the times following. Also were observed more stable values of SBP, DBP and MAP in CX group over the time, while the ISO group showed a decline of these parameters after hypovolemia. Except for PVC, there was no difference between the anesthetic protocols about the effects on cardiovascular function and blood count, chemistry and gas analysis of the recipients. Blood transfusion from donor anesthetized with ketamine and xylazine caused greater increase of the PVC of the recipients, when compared to transfusion of blood collected under anesthesia with isoflurane. It wasn t possible to establish an effective comparison between the protocols evaluated. Additional studies with larger number of animals and evidence of the presence of anesthetics in blood transfusions could clarify this issue. The proposed technique allowed to monitor effectively the arterial and venous blood pressures, although the risk of bleeding from accidental loss of the arterial catheter.